Dressing The Body In Captivity: a practice to reveal (Argentina 1976-1983) (ModaPalavra e-periódico, 2019)
In tune with proposals that intend to continue generating knowledge about the recent past in Argentina, this work presents the process of construction of a research project that starts from a perspective that is not frequently used to analyze the experience in clandestine centers during the years of the last military dictatorship in Argentina. We believe that it can be productive to visualize the different steps taken in the formulation of the work plan and the way in which diverse theoretical and methodological decisions led to configure an object of study that comes to interrogate a vacancy area in Argentine academic research. We refer, specifically, to the use of an approach that seeks to identify and study in the narratives, stories and testimonies about the captivity in clandestine detention centers, everything related to exchanges, transformations or mutations that the detained have produced in the clothes and fabrics that covered them with the ultimate purpose of revealing what senses these actions might have in the particular context of captivity.
Keywords: dressed body; resistance; captivity